2000
DOI: 10.1590/s0100-879x2000001000011
|View full text |Cite
|
Sign up to set email alerts
|

21-Hydroxylase deficiency in Brazil

Abstract: We determined the frequency of large rearrangements and point mutations in 130 Brazilian patients with 21-hydroxylase deficiency and correlated genotype with phenotype. The frequency of CYP21 deletions was lower (4.4%) than in most of the previous series described, whereas the frequency of large gene conversions was similar to the frequency reported in the literature (6.6%). The most frequent point mutations were I2 splice (41.8% in salt wasting -SW), I172N (32.6% in simple virilizing -SV) and V281L (40.2% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…O estudo dos grandes rearranjos e das mutações de ponto derivadas do pseudogene identificou mutações em 76 a 93% dos alelos na população brasileira com as formas clássica e não clássica da deficiência da 21 hidroxilase (18)(19)(20)(21)(22), indicando que os demais alelos devem conter mutações novas.…”
Section: Freqüência Das Mutações Na Populaçãounclassified
“…O estudo dos grandes rearranjos e das mutações de ponto derivadas do pseudogene identificou mutações em 76 a 93% dos alelos na população brasileira com as formas clássica e não clássica da deficiência da 21 hidroxilase (18)(19)(20)(21)(22), indicando que os demais alelos devem conter mutações novas.…”
Section: Freqüência Das Mutações Na Populaçãounclassified
“…The incidence of CYP21A2 mutations might vary among ethnic groups; previous studies observed a lower frequency of CYP21A2 deletions in the Brazilian population than in Caucasian subjects ( 17 ). Interestingly, a higher frequency of mutations in the founder effect gene, not derived from the pseudogene, was identified in the former individuals ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 95%
“…This genotype-phenotype correlation is useful in clinical practice to predict clinical form, especially for prenatal diagnosis and neonatal screening (12)(13)(14)(15). Still, a French study indicates that neonatal screening using serum 17-OHP levels has a low positive predictive value in special situations, such as in premature infants. That is, a significant false positives rate is observed, causing increased workload for health care systems and concern among parents (16).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos de seqüenciamento complementando as técnicas anteriores identificaram mutações em 100% dos alelos da forma clássica, enquanto que a forma não clássica, em nossa amostra, permanece ainda com fre- qüência alta (23%) de alelos sem mutações identificadas (29). Nenhum paciente portador de forma não clássica e com valor da 17OHP pós-ACTH <17ng/mL teve seu genótipo definido.…”
Section: Genética Molecularunclassified